1969
DOI: 10.1021/j100845a043
|View full text |Cite
|
Sign up to set email alerts
|

Thermal decomposition of perfluorocyclobutane in a single-pulse shock tube

Abstract: The thermal decomposition of perfluorocyclobutane was studied between 1100 and 1265°K behind reflected shock waves in a modified single-pulse shock tube using dilute c-CaFg-Ar mixtures. Reflected shock temperatures were evaluated from the Rankine-Hugoniot equations using measured incident and reflected shock velocities. Analyses were carried out by mass spectrometry and gas chromatography. The observed reaction product was almost exclusively CzF4 except at the highest temperatures where small amounts of C3Fa w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1970
1970
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 1 publication
2
15
0
Order By: Relevance
“…The absence of reliable thermochemical parameters for the C 4 F 8 isomers (see below) precludes any thermodynamic hypothesis concerning the apparent temperature dependence of their ratio. Cycloreversion of c-C 4 F 8 was observed under shock-tube conditions at 770-930 • C [32,33] and at 825-990 • C [34], as well as under adiabatic compression conditions at 725-875 • C [5]. Data from Bauer and Javanovic [20] on the formation of C 2 F 4 and C 3 F 6 in a micro-pilot plant in the 800 • C range were subject to significant fluctuations in temperature and pressure during reaction.…”
Section: High-temperature Regimementioning
confidence: 95%
“…The absence of reliable thermochemical parameters for the C 4 F 8 isomers (see below) precludes any thermodynamic hypothesis concerning the apparent temperature dependence of their ratio. Cycloreversion of c-C 4 F 8 was observed under shock-tube conditions at 770-930 • C [32,33] and at 825-990 • C [34], as well as under adiabatic compression conditions at 725-875 • C [5]. Data from Bauer and Javanovic [20] on the formation of C 2 F 4 and C 3 F 6 in a micro-pilot plant in the 800 • C range were subject to significant fluctuations in temperature and pressure during reaction.…”
Section: High-temperature Regimementioning
confidence: 95%
“…It has been observed in the case of ethane pyrolysis at 900°K [7a] that the decomposition of the ethyl radical is probably not in the first-order region, even at total pressures of 1 atm. Reactions (5) and (6) are very similar to ethyl radical decomposition; and, although a fourfold higher total pressure in this study will shift the reaction toward the high-pressure region, this might be somewhat offset by the higher temperatures used. It is therefore possible that these reactions are in a pressure-dependent region.…”
Section: Discussionmentioning
confidence: 77%
“…The expulsion of a hydrogen atom could give rise to one of the observed products, CF2CFCI, viz., (8) CF36HC1 -+ CFzCFCl + H Based on the known heats of formation [ 1 I ] of CFzCFC1 and CF2CFH, it can be shown that the difference in the heats of reaction at 298°K for reactions (8) and (5) is A ( A H ) 'v 22 kcal mol-'. On the basis of this evidence, we choose to ignore any contribution of reaction (8) to the yield of CFZCFC1.…”
Section: Elimination Reactionsmentioning
confidence: 99%
“…While all previous studies [6][7][8][9][10][11][12][13] used end product analysis and, in consequence, no direct observation of CF 2 was possible, it was difficult to unambigously identify the origin of C 3 F 6 .…”
Section: Physical Chemistry Chemical Physics Accepted Manuscriptmentioning
confidence: 99%
“…The latter played some role in earlier low temperature experiments using static reactors (see the discussion by Poutsma 1 ). They were avoided in previous shock wave experiments [11][12][13] which used the single pulse technique. However, there were considerable discrepancies in the results of these studies 12,13 which were attributed to shock wave nonidealities 13 .…”
Section: Physical Chemistry Chemical Physics Accepted Manuscriptmentioning
confidence: 99%